Peningkatan Perilaku Peduli Lingkungan Melalui Program Gemar Berseri di Kabupaten Karanganyar - Citra Tyas Laksmadita; Wisnu Sri Hertinjung; Dwi Arsinta Kusumawati (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2022)
A clean and healthy environment is the desire of the community, to achieve this requires continuous awareness and efforts from residents. Lack of awareness of maintaining cleanliness makes people vulnerable to health problems. This study aimed to determine the effectiveness of the Gemar Berseri Program in increasing environmental care behavior in the Dusun D community, Karanganyar Regency. This research is a quasi-experimental using one group pre-post-test design. Assistance and psychoeducation program for stakeholders and residents of Dusun D 185 residents. Analysis of the data using the Wilcoxon test with the results Z=-2.041 with p=0.041, which means that there is a significant difference in understanding of environmental care behavior before and after psychoeducation. The data can be analyzed qualitatively in the form of the formation of a Residential Feasibility Assessment Team. The Gemar Berseri program is effective in increasing public understanding of environmental care behavior. This program needs to be followed up continuously with real behavior in maintaining environmental cleanliness and health.